Oxidative cleavage of polysaccharides by a termite-derived superoxide dismutase boosts the degradation of biomass by glycoside hydrolases. Issue 12 (6th June 2022) - Franco Cairo, João Paulo L.; Mandelli, Fernanda; Tramontina, Robson; Cannella, David; Paradisi, Alessandro; Ciano, Luisa; Ferreira, Marcel R.; Liberato, Marcelo V.; Brenelli, Lívia B.; Gonçalves, Thiago A.; Rodrigues, Gisele N.; Alvarez, Thabata M.; et al.
Abstract : A Cu/Zn superoxide dismutase isolated from termite gut can oxidise glucose polymers, boosting the activity of glycoside hydrolases. Abstract : Wood-feeding termites effectively degrade plant biomass through enzymatic degradation. Despite their high efficiencies, however, individual glycoside hydrolases isolated from termites and their symbionts exhibit anomalously low effectiveness in lignocellulose degradation, suggesting hereto unknown enzymatic activities in their digestome. Herein, we demonstrate that an ancient redox-active enzyme encoded by the lower termite Coptotermes gestroi, a Cu/Zn superoxide dismutase ( Cg SOD-1), plays a previously unknown role in plant biomass degradation. We show that Cg SOD-1 transcripts and peptides are up-regulated in response to an increased level of lignocellulose recalcitrance and that Cg SOD-1 localizes in the lumen of the fore- and midguts of C. gestroi together with termite main cellulase, Cg EG-1-GH9. Cg SOD-1 boosts the saccharification of polysaccharides by Cg EG-1-GH9. We show that the boosting effect of C g SOD-1 involves an oxidative mechanism of action in which Cg SOD-1 generates reactive oxygen species that subsequently cleave the polysaccharide. SOD-type enzymes constitute a new addition to the growing family of oxidases, ones which are up-regulated when exposed to recalcitrant polysaccharides, and that are used by Nature for biomass degradation.